Hydrogeochemical Characterization and Usability Analysis of Deep Groundwater in the Eastern Part of Hetauda-Chitwan Dun Basin, Bagmati Province, Nepal - Rizal, Nirmal; Silwal, Champak Babu; Atreya, Adesh; Khatiwada, Manoj; Shakya, Nir (Journal of Institute of Science and Technology, 2024)
Groundwater is an essential commodity on which residents of the area are dependent for drinking and irrigation purposes. The study focuses on the evaluation of hydrogeochemistry and the suitability of groundwater for drinking and irrigation purposes in the eastern part of the Hetauda-Chitwan Dun Valley. Altogether, seventeen groundwater samples were collected from deep aquifers and analyzed for different physical and chemical constituents. The groundwater has been characterized as slightly acidic and soft. The dominant anions and cations are in the order of HCO3- > Cl- > SO42- > NO3- and Ca2+ > Na+ > Mg2+ > K+ respectively. The groundwater facies in the study area are dominantly the Ca-HCO3 type however some Ca-Mg-Cl facies were also identified. The groundwater chemistry in the area is predominantly governed by rock-water interaction where silicate weathering emerges as principal sources of ionic concentration. The analytical results compared with the National Drinking Water Quality Standard (NDWQS) show that all parameters lie within the permissible limit. The water samples fall under excellent to good classes in terms of drinking water quality index. Based on several indices like electrical conductivity (EC), salinity hazard (SH), sodium absorption ratio (SAR), and percent sodium (%Na) the groundwater is suitable for irrigation purposes. In contrast, magnesium ratio (MR) and soluble sodium percentage (SSP) show that 23.53% and 17.65% of the groundwater samples are unsuitable and doubtful for irrigation purposes, respectively. The outcome of the study can be better used for informed decision-making regarding water resource management and sustainable development in the evolving landscape of Hetauda Sub-metropolitan City.